Small states vulnerat[b]ility and resilience : lessons in diplomacy from a case sudy (Antigua and Barbuda vs the United States at the WTO) - Sanders, Sir Ronald ([CCS] [Georgetown]GY, 2009)
Uses this case study to show the vulnerability of a small state, the huge obstacles that it faces in trying to establish its rights in the international community, and the importance of diplomacy in seeking both to assert and win those rights.